Navigating north: how body mass and winds shape avian flight behaviours across a North American migratory flyway. (7th May 2018) - Horton, Kyle G.; Van Doren, Benjamin M.; La Sorte, Frank A.; Fink, Daniel; Sheldon, Daniel; Farnsworth, Andrew; Kelly, Jeffrey F.
Abstract: The migratory patterns of birds have been the focus of ecologists for millennia. What behavioural traits underlie these remarkably consistent movements? Addressing this question is central to advancing our understanding of migratory flight strategies and requires the integration of information across levels of biological organisation, e.g. species to communities. Here, we combine species‐specific observations from the eBird citizen‐science database with observations aggregated from weather surveillance radars during spring migration in central North America. Our results confirm a core prediction of migration theory at an unprecedented national scale: body mass predicts variation in flight strategies across latitudes, with larger‐bodied species flying faster and compensating more for wind drift. We also find evidence that migrants travelling northward earlier in the spring increasingly compensate for wind drift at higher latitudes. This integration of information across biological scales provides new insight into patterns and determinants of broad‐scale flight strategies of migratory birds.